Antileishmanial Evaluation and Phytochemical Screening of Iraqi Sanchezia speciosa Petroleum Ether Fraction in vitro - Muntadher Salim Rasool; Abdul-Jaleel, Thukaa Zuhair (Iraqi Journal of Pharmaceutical Sciences, 2025)
Leishmaniasis is a significant parasite issue. Vaccine inaccessibility and the absence of a safe and effective therapy that is not resistant to the illness hinders the total eradication of this disease and remains a challenge for the control of the disease; medications with harmful side effects or insufficient efficacy have resulted in disease recurrence.The path towards discovering alternative medications derived from natural resources with shown antileishmanial activity has been paved using these criteria. Consequently, two Leishmanial parasites were examined for their antileishmanial activity, and an Iraqi plant was chosen. The anti-leishmania fraction activity was obtained from the aerial portions of Sanchezia speciosa, which has been assessed using in vitro methods.Maceration of the aerial portions of Sanchezia speciosa with petroleum ether was used to create the extract, which included active non-polar compound components. To ensure accuracy, an MTT assay was utilized and the extract was prepared as six distinct concentrations with 1% DMSO, the medium with parasite serving as negative controls and Pentostam ( Sodium stibogluconate ) as positive controls. Leishmania donovani and Leishmania tropica were both tested for their ability to be effectively inhibited by the fraction that was obtained. Based on the extract of the plants at many doses tested, the results showed superior antileishmanial activity of macerated petroleum ether fraction with IC50 value (0.092 mg/ml) against Leishmania tropica and IC50 value (0.074 mg/ml) against Leishmania donovani when combined with the antileishmanial activity of the official treatment medication (Pentostam®); the chemical examination of the extracts revealed the presence of terpenes and steroids by qualitative phytochemical tests. The findings of this study indicate that the presence of certain secondary metabolites, such as terpene and steroid compounds in the materials utilized to make up this fraction likely explains this high potential antileishmanial action against Leishmania tropica and Leishmania donovani. Ongoing efforts are being made to find a successful approach for treating leishmaniasis with minimal side effects, and there is a significant focus on herbal medications.